Pregnancy in Budd-Chiari Syndrome: Case Report and Proposed Risk Score. Issue 22 (May 2016) - Merz, Waltraut M.; Rüland, Anna M.; Hippe, Valeria; Poetzsch, Bernd; Meyer, Carsten; Pollok, Joerg M.; Gembruch, Ulrich; Trebicka, Jonel
Abstract : Abstract: Due to its rarity, experience with pregnancy in Budd–Chiari syndrome (BCS) is limited. With the advent of new treatment modalities, transjugular intrahepatic portosystemic shunt in particular, numbers of affected women seeking pregnancy with BCS are expected to rise. Here, we use a case that ended lethal within 2 years after delivery to discuss the effect of pregnancy on BCS and vice versa, and to highlight the necessity of a multidisciplinary teamwork. Additionally, a risk classification is proposed which may serve as a framework for preconception counseling and assist in the establishment and evaluation of treatment algorithms; its criteria need to be defined and assessed for their applicability in further studies.